Increasing Knowledge In The Health Protocol Of Covid-19 Prevention With Health Education In Boarding Schools - Ikbal Fradianto; Djoko Priyono; Nita Arisanti Yulanda; Arief Andriyanto (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: The COVID-19 pandemic that has occurred in the world has also impacted the world of education. The school’s policy initially closed face-to-face activities, but over time allowed schools to return to holding face-to-face school activities on the condition that they have to implement health protocol. Implementing the health protocol is essential for all students to do in schools to prevent the transmission of COVID-19 in the school environment. The implementation of the health protocol starts from the knowledge that students must have; therefore, there needs to be additional efforts to improve students’ knowledge. Actions that can be made in students’ knowledge suitable are by providing health education. This study aims to provide education about implementing the COVID-19 prevention health protocol on changes in knowledge. Methods: The methodology used in this study was quasi-experimental without using a control group; the statistical test used was paired t-test. Results: The results of this study indicate a change in knowledge between before being given education and after that with a P-value <0.005. Conclusion: There is an effect of providing education to increase knowledge in the health protocol of COVID-19 prevention.